Safeguards and antidumping in Latin American trade liberalization - Finger, Joseph M., 1939- 1939- (Policy research working paper, 2008)
"The binding of tariff rates and adoption of the General Agreement on Tariffs and Trade/World Trade Organization-sanctioned safeguards and antidumping mechanisms provided the basis to remove a multitude of instruments of protection in the Latin American countries discussed in this paper. At the same time, they helped in maintaining centralized control over the management of pressures for protection in agencies with economy-wide accountabilities. The World Trade Organization's procedural requirements (for example, to follow published criteria, or participation by interested parties) helped leaders to change the culture of decision-making from one based on relationships to one based on objective criteria. However, when Latin American governments attempted to introduce economic sense - such as base price comparisons on an economically sensible measure of long-run international price rather than the more generous constructed cost concept that is the core of WTO rules - protection-seekers used the rules against them. They pointed out that World Trade Organization rules do not require the use of such criteria, nor do procedures in leading users (industrial countries) include such criteria. In sum, the administrative content of the rules supported liberalization; the economic content did not. "--World Bank web site